2021
DOI: 10.3390/agriculture11121184
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Root Distribution and Improving Water Use Efficiency via Drip Irrigation in a Jujube (Zizyphus jujube Mill.) Orchard after Long-Term Flood Irrigation

Abstract: Jujube tree yields in dryland saline soils are restricted by water shortages and soil salinity. Converting traditional flood irrigation to drip irrigation would solve water deficit and salt stress. The root distribution reacts primarily to the availability of water and nutrients. However, there is little information about the response of jujube roots to the change from flood irrigation to drip irrigation. In this context, a two–year experiment was carried out to reveal the effects of the change from long–term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Significant changes in water content at different soil depths with changes in flow rate and duration were associated with proper distribution and longer water opportunity times. This conclusion is similar to that of Sun et al 14 and Li et al 97 . Soil vertical wetting circle expanded to more than 20 cm in 120 min of water flow.…”
Section: Discussionsupporting
confidence: 93%
“…Significant changes in water content at different soil depths with changes in flow rate and duration were associated with proper distribution and longer water opportunity times. This conclusion is similar to that of Sun et al 14 and Li et al 97 . Soil vertical wetting circle expanded to more than 20 cm in 120 min of water flow.…”
Section: Discussionsupporting
confidence: 93%
“…After crop replacement, the comprehensive benefits of drip irrigation treatments were higher than those of flood irrigation treatments. The reason for the observation could be that drip irrigation can effectively improve water and nutrient utilization efficiency when compared to flood irrigation [43], which enhances the growth and development of crops, as well as ADMQ accumulation, and increases crop yield, thereby resulting in higher RLDs under drip irrigation treatments than those observed under flood irrigation treatments. Maize RLD did not contribute significantly toward PC1 in 2020, although all nine indicators contributed significantly toward PC1 in 2021.…”
Section: Impact Of Water and Fertilizer Regulation On The Overall Ben...mentioning
confidence: 99%
“…One previous study reported that DI aided during the cell expansion period of jujube fruit growth to conserve water while ensuring that the fruit receives adequate moisture (Wang et al, 2021). Another study revealed that DI could reconstruct the root distribution of jujube trees and improve water use efficiency (Li et al, 2021). Moreover, one study has been performed on appropriate water and fertilizer scheduling that can significantly improve the yield of jujube trees after flood irrigation changed to DI (Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%